If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + -26 = 36 Reorder the terms: -26 + 9m = 36 Solving -26 + 9m = 36 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 9m = 36 + 26 Combine like terms: -26 + 26 = 0 0 + 9m = 36 + 26 9m = 36 + 26 Combine like terms: 36 + 26 = 62 9m = 62 Divide each side by '9'. m = 6.888888889 Simplifying m = 6.888888889
| 25x^2+4y^2-6=0 | | f(0)=2(2x-5)+6(2x+6) | | 1/3*6= | | z+-40=36 | | 23-2(3+4)= | | 2(3x-1)-2x=7x+3 | | 3x+3=3x+15-5 | | 4+2X=10-4X | | 37x*0.6=77.7 | | Xy-3y-y=0 | | 2(5-8x)-5=5(2x+1) | | x^3+0x^2-3x+2=0 | | 14n=13a-11 | | w+-48=-23 | | Tn=2(3n-2) | | x^2+8*x-180=0 | | 0.08x+1.72=0.06x+1.68 | | 11in+3in=x | | -5(2x-1)+6=21 | | 3x+1/5=2x/3 | | 0.6r=-72 | | 2(pi)+d=5(pi) | | 1+r+r^2+r^3+r^4=0 | | 10=50x+10x | | ln(x)+ln(2)=ln(14) | | 9x+14-8x=-3-10 | | (16+3x)8+(X-11)3=21 | | 15+3x=24 | | 11y^2+3=0 | | 5x-53=2 | | 61y=30(2y+14) | | Sin^2x-2sinx=k |